Improving the efficiency of developing students’ foreign language written competence at technical universities - Fandieieva, A.; Chevychelova , Ye. (Problems of Engineer-Pedagogical Education, 2021)
The article discusses the issues of increasing the effectiveness of developing students’ foreign language written competence at higher technical education institutions. Taking into account the growing requirements for students’ writing skills in a foreign language, the great potential of creative writing for increasing the level of foreign language proficiency and the lack of developed systems of exercises for its teaching, the authors offer a staged approach to the formation of written communicative competence. The specific features of each subsequent stage consist in increasing the volume of narrative writing, expanding topics and communication problems, increasing the information content of the texts as well as the degree of students' independence in the process of their own writing. Much attention is paid to combining writing and reading as types of speech activity. In particular, the authors offer foreign language teachers a number of techniques that can enhance teaching creative writing. The article considers in detail the principles of working with exemplar texts, which clearly illustrate specific features of effective writing, and assignments that can help students develop the ability to formulate their thoughts and write argumentative pieces. The authors also emphasise the effectiveness of using strategies like RAFT to develop critical thinking for writing original texts. It is noted that the main problem that may arise during the implementation of the offered techniques and principles is that students have trouble understanding texts for reading, let alone create their own pieces of writing. This problem can be solved by the staged approach to the implementation of these principles in the educational process. The issues of developing students’ foreign language writing skills require further consideration, since writing has an enormous developmental potential, which, unfortunately, has not yet been properly used in teaching foreign languages, especially with regard to teaching foreign creative writing at a technical university.